1993
DOI: 10.1111/j.1600-0773.1993.tb01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Treatment of Panic Disorder

Abstract: Drug treatment of panic disorder is reviewed with focus on recent controlled studies. The efficacy of alprazolam, a triazolobenzodiazepine, and imipramine, a tricyclic antidepressant, has consistently been demonstrated, but there is reasonable evidence that other benzodiazepines or antidepressants might also be effective if equipotent doses are used. Most controlled studies demonstrate drug efficacy on several psychopathological symptoms, including the core symptom panic attacks. Limited evidence indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…The present study supports the consistent finding in the literature that imipramine is more effective than placebo in the treatment of Panic Disorder (e.g., Rosenberg, 1993). Apart from the limited attack change score, all the 95% CI for the outcome variables are positive and in favour of imipramine compared to placebo.…”
Section: Discussionsupporting
confidence: 92%
“…The present study supports the consistent finding in the literature that imipramine is more effective than placebo in the treatment of Panic Disorder (e.g., Rosenberg, 1993). Apart from the limited attack change score, all the 95% CI for the outcome variables are positive and in favour of imipramine compared to placebo.…”
Section: Discussionsupporting
confidence: 92%
“…49,50 While the present study was underway, we found in a separate series of experiments, that chronic treatment with various benzodiazepine-site ligands produces transient changes in GABA A receptor mRNA levels. 41 This finding suggests the possibility that alprazolam causes its effects on GABA A receptor gene expression at an earlier time period than 21 days in a similarly transient manner.…”
Section: Resultsmentioning
confidence: 67%
“…Indeed, previous data have indicated that ␣3␤1␥2 receptors display lower GABA-gated maximal current amplitudes and higher GABA EC 50 values compared to many other receptor subtypes. [55][56][57][58][59][60] Hence, the substitution of a given receptor subtype for the ␣3␤1␥2 subunit combination may decrease GABAergic inhibition, while a change in the total number of GABA A receptors would alter GABAergic tone at a particular synapse in a similar manner.…”
Section: −1mentioning
confidence: 97%
“…Ample evidence shows that pharmacological treatments are effective in reducing the symptoms of panic disorder and panic disorder with agoraphobia, including panic attacks, phobic avoidance, and anticipatory anxiety, and the occupational and social disability associated with panic disorder (Ballenger, 1993;Keller et al, 1993;Lepola, Rimon, & Riekkinen, 1993;Rosenberg, 1993). There is evidence that some drugs are more effective in treating panic attacks, whereas others are more effective in reducing phobic avoidance or anticipatory anxiety (Rosenberg, 1993).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…There is evidence that some drugs are more effective in treating panic attacks, whereas others are more effective in reducing phobic avoidance or anticipatory anxiety (Rosenberg, 1993). Basoglu et al (1994) studied the relationship between panic attacks, anticipatory anxiety, and phobic avoidance in individuals treated for panic disorder.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%